The effect of applying the kaizen concept to increase efficiency in reducing waiting time of service for physical therapy department case study Panyananthaphikkhu Chonprathan Medical Center - Jitreengarm, Jiranant; Sudharatna, Yuraporn (Journal for Strategy and Enterprise Competitiveness, 2023)
The objectives of this research were 1) to study the process and procedure for receiving services, 2) to compare the waiting time of service users before and after using the waiting time reduction guideline, and 3) to suggest ways to increase efficiency in service delivery. Serve to reduce the waiting time of the physical therapy department Panyananthaphikkhu Medical Center, Chonprathan, Srinakharinwirot University. Apply Kaizen Theory, 5W1H, and ECRS as tools to help find method problems and improve them to reduce useless processes. The sample was Patients receiving services in the physical therapy department Panyananthaphikkhu Medical Center, Chonprathan, Srinakharinwirot University. The samples were randomly selected according to their qualifications, 30 people were analyzed and compared the results before and after the improvement. Collect waiting time information and satisfaction before and after improvement. Statistics used for data analysis were percentage, mean and standard deviation. The results of using Kaizen practices found that the average waiting time after process improvement and service procedures, waiting time from physical therapists, time was reduced from 25 minutes to 15 minutes (40% reduction). Total waiting time (Start to finish, excluding the procedure) decreased from 145 minutes to only 109 minutes (reduced 36 minutes, representing 24.83%) and the average score of satisfaction after the improvement was higher than before the improvement. The researcher proposed that health service workers should pay attention to reducing the wastage caused by waiting for services. To increase customer satisfaction will benefit the efficiency and service standards of the hospital in the future.